CGIAR Contributions and Climate Change Classification - Esponda Bernal, Maria Del Mar; Amahnui, George Amenchwi; Andrade López, Robert Santiago (2024)
It includes the 36 Golden Eggs, along with the 61 innovative breakthroughs classified by their relation with Climate change approaches Methodology: In order to analyze the innovations developed by the CGIAR to determine whether they were aimed at climate change adaptation or mitigation (or both), the dataset was meticulously compiled from two different sources. First, we examined the esteemed publication entitled "36 Golden Eggs for the 2021 Transfer Market Place." These 36 notable research assets were carefully selected during a virtual forum held in June 2021. This forum brought together current custodians of the esteemed CGIAR scientific community, fostering multiple discussion sessions aimed at prioritizing these assets (2024-01). Second, the 61 innovative breakthroughs were included, dubbed the 50 years of CGIAR innovations that changed the world.